A framework for application of renewable energy in urban water systems (Advances in Civil and Architectural Engineering, 2021)
This paper presents possible concepts of using renewable energy sources (RESs) in urban water systems (UWSs). The hydro and biomass energy generated by UWSs are typical renewable sources of energy, but these have limited capacity. Solar and wind energy sources are standard global RESs characterized by large capacity and intermittent production. However, technological challenges associated with the use of the sun and wind means that these sources cannot directly and continuously supply a UWS with electric energy. Thus, it is necessary to hybridize them with conventional sources through the electric energy grid system or the use of electric energy storage (EES) including pump storage hydroelectric (PSH) plants. The analysis presented in the paper determined that green energy is possible and relatively easy to implement in a UWS. The use of RESs contributes to the straightening of urban energy sustainability and the reduction of CO2 emissions from UWSs.